Identifying key risk factors for Chinese international students: a hybrid AHP–DEMATEL–cross-reinforcement matrix approach with policy implications - Li, Hongwei; Wang, Lei; Gao, Junhong (Frontiers in Sociology, 2025)
Chinese students usually face risks from various aspects in the process of studying abroad. The use of the analytic hierarchy process alone ignores the interplay between the influencing factors and lacks systematic thinking about the identification of key influencing factors due to the intricacies of the factors affecting and constraining these risks. Therefore, we utilize the DEMATEL method and cross-reinforcement matrix to improve the weights obtained from AHP and to enhance the accuracy and scientific rigor of the weight vectors. Finally, five factors with the largest weights of risk factors affecting international students are identified through the analysis. They are self-management ability, language ability, policy of the host country, economic conditions of the host country, and values. Appropriate risk response countermeasures are proposed to reduce the risk potential of international students based on the results. Exploring the risk factors affecting students studying abroad can provide a reference for Chinese students to predict and control the risks of studying abroad. It can also provide support for international institutions to recruit, manage, and assist Chinese students.